Structural and electronic properties of 2,2′,6,6′-tetraphenyl-dipyranylidene and its use as a hole-collecting interfacial layer in organic solar cells - Courté, Marc Patrick (2017)
The accumulation of positive charges at the anodic interface considerably limits the efficiency of photovoltaic solar cells based on polymer/fullerene bulk heterojunctions (BHJs). Interfacial layers (IFLs) such as PEDOT:PSS improve charge injection but have no effect on the unbalanced electron/hole transport across the BHJ. We report here the use of 2,2′,6,6′-tetraphenyl-dipyranylidene (DIPO-Ph4), a planar quinoïd compound, as an efficient anodic IFL in organic solar cells based on BHJs made of poly(3-hexylthiophene)/[6,6]-phenyl-C61-butyric-acid-methyl-ester (P3HT:PCBM). When deposited under vacuum onto a glass substrate, DIPO-Ph4 thin films are constituted of densely packed and vertically aligned crystalline needles. Current-sensing atomic force microscopy (CS-AFM) reveals a considerable increase of the hole-carrying pathways in DIPO-Ph4 thin films as compare to PEDOT:PSS, thus revealing their hole transporting/electron blocking properties. Inserting a 10 nm thick IFL of DIPO-Ph4 in combination with a 5 nm thick PEDOT:PSS between the ITO electrode and the P3HT:PCBM film leads to photocurrent densities up to 11.5 mA/cm2 under AM 1.5G and conversion efficiencies up to 4.6%, that is substantially higher than PEDOT:PSS-only devices.